Transvaginal/Transumbilical Hybrid—NOTES—Versus 3-Trocar Needlescopic Cholecystectomy: Short-term Results of a Randomized Clinical Trial. Issue 3 (March 2015) - Bulian, Dirk Rolf; Knuth, Jürgen; Cerasani, Nicola; Sauerwald, Axel; Lefering, Rolf; Heiss, Markus Maria
Abstract : Objective: For cholecystectomy, both the needlescopic cholecystectomy (NC) 3-trocar technique using 2 to 3 mm trocars and the umbilical-assisted transvaginal cholecystectomy (TVC) technique have found their way into clinical routine. This study compares these 2 techniques in female patients who are in need of an elective cholecystectomy. Background: Natural orifice transluminal endoscopic surgery (NOTES) is a surgical concept permitting scarless intra-abdominal operations through natural orifices, such as the vagina. Because of the lack of an adequately powered trial, we designed this first randomized controlled study for the comparison of TVC and NC. Methods: This prospective, randomized, nonblinded, single-center trial evaluates the safety and effectiveness of TVC (intervention), compared with NC (control) in female patients with symptomatic cholecystolithiasis. The primary endpoint was intensity of pain until the morning of postoperative day (POD) 2. Secondary outcomes were among others intra- and postoperative complications, procedural time, amount of analgesics used, pain intensity until POD 10, duration of hospital stay, satisfaction with the aesthetic result, and quality of life on POD 10 as quantified with the Eypasch Gastrointestinal Quality of Life Index (GIQLI). Results: Between February 2010 and June 2012, 40 patients were randomly assigned to the interventional or control group. All patients completed follow-up. Procedural time, length of postoperative hospital stay, and the rate of intra- and postoperative complications were similar in the 2 groups. However, significant advantages were found for the transvaginal access regarding pain until POD 2, but also until POD 10 ( P = 0.043 vs P = 0.010) despite significantly less use of peripheral analgesics ( P = 0.019). In the TVC group, patients were significantly more satisfied with the aesthetic result ( P < 0.001) and had a significantly better GIQLI ( P = 0.028). Conclusions: Although comparable in terms of safety, TVC caused less pain, increased satisfaction with the aesthetic result, and improved postoperative quality of life in the short term. Abstract : In a randomized clinical trial, needlescopic 3-trocar cholecystectomy was compared with transvaginal/transumbilical hybrid—NOTES—technique for symptomatic cholecystolithiasis. We found significantly less pain despite less analgesics, increased satisfaction with the aesthetic result, and improved postoperative quality of life in the NOTES group. Furthermore, both techniques were equal in terms of safety.